The retinal nerve fiber layer thickness is useful for the assessment of diabetic retinopathy severity - Zulvikar Syambani Ulhaq; Yuliono Trika Nur Hasan; Sarah Herawangsa; Mohamad Ahnaf Audris; Muhammad Fauzan Al Farizy; Rafli Dhafa Aditya; Ratu Belqys Rosadeila Putri (Diabetes Epidemiology and Management, 2022)
Objective: To assess the alterations of individual retinal layer thickness at different stages of diabetic retinopathy (DR) and its role in determining DR severity. Methods: In this study, 51 patients with nonproliferative DR (NPDR) and 57 patients with proliferative DR (PDR) were enrolled. The individual retinal layer thickness was measured according to the image segmentation of the macular scan collected from the optical coherence tomography (OCT) result. Comparative analysis was performed in addition to assessment of the diagnostic performance of the retina layer using receiver-operating-curve (ROC) analysis. Moreover, correlation analysis was conducted to examine the association between HbA1c and retina layer changes. Results: In PDR subjects, the retinal nerve fiber layer (RNFL, p < 0.0001), ganglion cell layer (GCL, p < 0.0001), inner plexiform layer (IPL, p = 0.0025), ganglion cell-inner plexiform layer (GC-IPL, p < 0.0001), and ganglion cell complex (GCC = RNFL+GCL+IPL, p < 0.0001) thickness were decreased compared to NPDR subjects. RNFL exhibited a better performance than GCL, GC-IPL, or GCC (AUC for RNFL = 0.76, p < 0.0001) in discriminating DR severity (cut-off of 16.62 μm (84.21% sensitivity and 70.59% specificity). The RNFL, GCL, IPL, GC-IPL, GCC, inner nuclear layer (INL), and total retinal layer (TLR) thickness correlated negatively with HbA1c levels in PDR group. Conclusion: Measurement of retinal degeneration, particularly by evaluating RNFL thinning is potentially useful for early identification of DR progression.